Differential encoding in prefrontal cortex projection neuron classes across cognitive tasks - Lui, Jan H; Nguyen, Nghia D; Grutzner, Sophie M; Darmanis, Spyros; Peixoto, Diogo; Wagner, Mark J; Allen, William E; Kebschull, Justus M; Richman, Ethan B; Ren, Jing; Newsome, William T; Quake, Stephen R; et al. (bioRxiv, 2020)
2+-activity of the molecularly homogeneous PFC→PAG type against two heterogeneous classes in several two-alternative choice tasks in freely-moving mice, we found that all task-related signals assayed were qualitatively present in all examined classes. However, PAG-projecting neurons most potently encoded choice in cued tasks, whereas contralateral PFC-projecting neurons most potently encoded reward context in an uncued task. Thus, task signals are organized redundantly, but with clear quantitative biases across cells of specific molecular-anatomical characteristics. Competing Interest Statement The authors have declared no competing interest. Footnotes * ↵8 Lead Contact